EXPLORING FINANCIAL TECHNOLOGY’S IMPACT ON GENERATION Z TRANSACTION KNOWLEDGE - Samuel PD Anantadjaya; Barick Ahmad Setiawan; Vivid Violin; Irwan Moridu; Muhsin N. Bailusy (Sean Institute, 2023)
This study examines the effect of Financial Technology (FinTech) on Generation Z's transactional knowledge as it relates to their digitally supported daily financial activities. A total of 57 randomly selected respondents completed an online questionnaire to collect data. The results of the data analysis indicate that the majority of respondents are female (91,2%) and between the ages of 17 and 25 (96%) (95%). Approximately 75.4% of respondents favor cash transactions, while 87.7% are aware of cashless transactions. The majority of respondents use various e-wallet applications, with OVO, DANA, and ShopeePay being the most popular options. E-wallets are predominantly used for online purchasing (35 respondents), although a small percentage also use them for consumptive shopping, credit purchases, money transfers, and game top-ups. The majority of respondents selected transactional features, such as fund transfers, as the most important aspects of fintech platforms. The results indicate that Generation Z has a solid grasp of Financial Technology and has actively adopted it in their financial activities.